Crisis-Related Measures in the Financial System and Sovereign Balance Sheet Risks. (Policy Papers; Policy Paper ;, 2009)
This paper examines the fiscal and financial risk implications of support measures in a sovereign balance sheet framework, making the point that the ultimate fiscal cost will depend on how balance sheets are managed-both in the near-term and as governments develop unwinding strategies. It suggests some key principles for efficient and transparent management of new assets, liabilities, and associated risks, and for moving toward an orderly disengagement.